China's Stronger Enforcement of the Anti-Monopoly Law and Korea's Response - Jaehyung Lee (Korea Development Institute (KDI), 2016)
Tougher enforcement of the anti-monopoly law in China is expected to open markets and bolster the competition environment. In response, Korean companies must make efforts to take full advantage these changes to expand their business into the Chinese market while avoiding the risk of violating the stricter laws. - China's enactment of the anti-monopoly law is considered a leap forward towards a market economy. - China adopted a market economy, but still emphasizes the role of government. - China's market structure is highly competitive although there exists institutional imperfections that disturb the efficiency of market functions. - Anti-monopoly law, price law and anti-unfair competition law constitute China's competition laws. - China's anti-monopoly law is a medium through which to develop a socialist market economy. - China's anti-monopoly law corresponds to global standards but "impartiality" has become the highest legal purpose and the basis for illegality. - China has shown strong willingness to correct administrative monopolistic practices, but the institutional mechanisms to make this happen are not yet properly established. - Illegal practices are subject to severe sanctions; Qualcomm was fined approximately RMB 6 billion (1.37 trillion won). - China has actively applied its anti-monopoly law to cases of international cartels and business combinations with foreign - companies. - It has been pointed out that China's law enforcement has problems including lack of independence, forced investigations and excessive discretionary power. - China will likely further strengthen the enforcement of the anti-monopoly law. - China's stricter antimonopoly law must be viewed positively and Korea should actively work to adapt. - China's anti-monopoly law considers excessively high prices to be a violation, and business combinations are reviewed based on industrial policy considerations. - In the long-term, stricter enforcement will provide more opportunities for Korean companies as it increases openness and transparency and removes competition-restricting regulations in the Chinese market.
Keywords: 330